ANALISA PERBEDAAN PENGGUNAAN PASIR SEBAGAI AGREGAT HALUS TERHADAP NILAI KUAT TEKAN BETON (Pasir Sungai lau-Hata Liquica dan Laklo Liquica dengan Kuat Tekan Beton Rencana 25 MPa dan 30 MPa) - Martinho Madeira Soares; Made Yani Anggreni; Egidius Salu (Jurnal Teknik Gradien, 2023)
Sand from Lau-Hata and Laklo rivers is widely used as a concrete mixture for construction by the community, there are buildings, highways, and culverts. However, research on the quality and specifications of these aggregates is still minimal. For this reason, in this study an analysis and experimental was attempted on the use of fine aggregate from Lau-Hata and Laklo river as a filler in the concrete mix. The purpose of this study was to find out how to compare aggregate specifications from the Lau-Hata and Laklo river and how the results of the compressive strength value of concrete. Experimental study method applied in this study. And conducted a comparative test of the specifications of fine aggregate from Lau-Hata and Laklo river. This study only to know the specifications of fine aggregates and trying to determine the quality of the concrete produced by the use of these filler with compressive strength value. The result of the research, these fine aggregates can be used as concrete filler but it’s just need special treatment such as washing the sand first to reduce silt content. The result of the compressive strength of concrete obtained and have similar value with compressive strength design. From design 25 MPa and 30 MPa, the concrete using Lau-Hata sand produce compressive strength of 25,6 MPa and 30 MPa. And concrete using Laklo sand produce compressive strength of 25,7 MPa and 30,5 MPa.